Pendidikan Kesehatan Ibu Hamil Tentang Ketidaknyamanan Pada Kehamilan Trimester I dan Penatalaksanaannya - Meti Patimah (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2020)
Pregnancy is a new experience for a woman, physical and psychological changes and social change raises anxiety. Anxiety in expectant mothers is influenced by several factors including knowledge. The condition of the mother's knowledge is lacking due to lack of experience and insufficient information will be complaints that may occur in the I trimester and how to handle it. The purpose of this activity is to increase the knowledge of the I trimester of pregnant women about the discomfort in the I trimester of pregnancy and its handling, data collection is conducted with posttest assessment in pregnant women after administration of education. Results showed that the knowledge of pregnant women about the discomfort in the I trimester and the handling of 55% of the category is adequate and 45% in good category. The health education activities continue to be carried out comprehensively.